A review of current calibration and validation practices in land-change modeling. (August 2016) - van Vliet, Jasper; Bregt, Arnold K.; Brown, Daniel G.; van Delden, Hedwig; Heckbert, Scott; Verburg, Peter H.
Abstract: Land-change models are increasingly used to explore land-change dynamics, as well as for policy analyses and scenario studies. In this paper we review calibration and validation approaches adopted for recently published applications of land-change models. We found that statistical analyses and automated procedures are the two most common calibration approaches, while expert knowledge, manual calibration, and transfer of parameters from other applications are less frequently used. Validation of model results is predominantly based on locational accuracy assessment, while a small fraction of the applications assessed the accuracy of the generated land-use or land-cover patterns. Of the reviewed model applications, thirty-one percent did not report any validation. We argue that to mature as a scientific tool, and to gain credibility for scenario studies and policy assessments, the validation of land-change models requires consideration of challenges posed by uncertainty, complexity, and non-stationarity of land-change processes, and equifinality and multifinality of land-change models. Highlights: We describe a commonly used framework for the development of land-change models We systematically reviewed the calibration and validation of recent applications Calibration is mostly based on automated procedures and statistical analyses Validation is mostly based on location accuracy and much less on pattern accuracy The experimentation period is often longer than the calibration and validation period